2012
DOI: 10.1108/03055721211227273
|View full text |Cite
|
Sign up to set email alerts
|

Value co‐creation through collective intelligence in the public sector

Abstract: Purpose -On the basis of the Collective Intelligence Genome framework, which was developed to describe private, for profit ventures, this study aims to review the recent public sector initiatives launched by the American federal government and the European Union. The study's goal is to examine if, and how, the Genome construct would apply to not for profit. Design/methodology/approach -This paper builds on an existing classification methodology for collective intelligence initiatives and extends it to pubic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 32 publications
0
33
0
4
Order By: Relevance
“…The appointment of block leaders in neighborhoods may also lead to greater coproduction in the form of recycling behaviors (Bovaird ). Citizens may also be willing to coproduce because of personal traits (Sundeen ), moral convictions (Wise, Paton, and Gegenhuber ), or a feeling of contributing to a cause (Bovaird et al ).
The coproduction of any government service will not only reduce costs but also enhance the quality and quantity of services received by the citizenry.
…”
Section: Recycling and Coproductionmentioning
confidence: 99%
“…The appointment of block leaders in neighborhoods may also lead to greater coproduction in the form of recycling behaviors (Bovaird ). Citizens may also be willing to coproduce because of personal traits (Sundeen ), moral convictions (Wise, Paton, and Gegenhuber ), or a feeling of contributing to a cause (Bovaird et al ).
The coproduction of any government service will not only reduce costs but also enhance the quality and quantity of services received by the citizenry.
…”
Section: Recycling and Coproductionmentioning
confidence: 99%
“…We categorize identified motivators broadly into intrinsic and extrinsic motivators (Loeffler and Bovaird ). Intrinsic motivators touch on the desire to achieve one's ethical values (Alford ), such as loyalty, solidarity, and a feeling of civic duty (Wise, Paton, and Gegenhuber ). The coproduction literature shows numerous examples where coproduction efforts of citizens are based on intrinsic motivators, ranging from supporting Roma (Schafft and Brown ), participating in child care services (Pestoff ), or promoting asylum seeker integration (Strokosch and Osborne ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Co-creation is also developing within public policy reform as a process that allows citizens to actively engage in the planning and delivery of public services (Osborne, Radnor & Strokosch, 2016). In the United States, several initiatives including the Veterans Benefits Administration Innovation Initiative and Innovation.ed.gov encourage individuals to put forth ideas, feedback, and harness their collective intelligence to create value (Wise, Paton, Gegenhuber, 2012). However, co-creation may not develop within the public sector along the lines it has developed in the private sector.…”
Section: Sector Adoptionmentioning
confidence: 99%
“…However, co-creation may not develop within the public sector along the lines it has developed in the private sector. This is because in the public sector, individuals may contribute because of financial rewards or notoriety, yet research in the public sector has shown individuals are motivated more by intrinsic rewards such as civic duty (Wise, Paton, Gegenhuber, 2012). Moreover, Osborne, Radnor and Strokosch note that co-creation within public services is unique to other forms as it is not a supplementary service or process, but rather public service delivery stands on the basic premise that it should be co-creation and/or co-produced with the community.…”
Section: Sector Adoptionmentioning
confidence: 99%